Gelatin Hasil Transformasi Kulit Ikan Patin (Pangasius hypohthalmus) sebagai Gelling Agent dalam Formulasi Gel Piroksikam - Muslim Suardi (LPPM Universitas Abdurrab, 2024)
Piroxicam is an effective non-steroidal anti-inflammatory drug, but it has serious side effects orally. The research was conducted to formulate piroxicam in gel dosage form using gelatin transformed from catfish skin (Pangasius hypophthalmus) as a gelling agent. Using this ingredient transformed from pig and cow is unacceptable for certain religious adherents. This study aims were to formulate piroxicam gel and determine the release of piroxicam from gel at various concentrations of 0.75, 0.875, and 1%, while innovator product (F4) was used as a positive control. The evaluations performed were organoleptic, homogeneity, pH, spreadability, and release profile. The release of piroxicam from the gel produced was conducted using a modified paddle-type dissolution device equipped with an eggshell membrane placed on a metal disk. The level of piroxicam dissolved was measured using a UV spectrophotometer at Î»max of 356.4 nm. The release kinetics of piroxicam gel formulas F1, F2, F3 and F4 followed zero-order kinetics model. The dissolution efficiency and T90 from formulas F1, F2, F3, and F4 value were highly significant differences (p < 0.01), while the dissolution rate were significant differences (p < 0.05). All of formula fulfill the requirements except spreadability characteristic.